Meraih Keunggulan Kompetitif Berkelanjutan Melalui Pengintegrasian Fungsi Sumber Daya Manusia dalam Strategi Bisnis - Lina Anatan (Universitas Kristen Maranatha, 2005)
To date, the business environment is more and more dynamic, turbulence, and increasingly competitive. Enterprises as business performer require the role of high quality and competence human resource or employee to response the development of business environment. The implementation of management and investment in human resource as one of competitive advantage sources are crucial. It may be due to human resource is subject or performer in the enterprise operational activity that use and manage other resources. Through human resource, entreprise can make business strategy and implement it to survive and to win the business competition. The business performer capability in managing and applying the competence based human resource is the key of enterprise success in winning the business competition.